2013
DOI: 10.1155/2013/256758
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Microhardness of Cu‐Ta Joints Produced by Explosive Welding

Abstract: The structure and microhardness of Cu-Ta joints produced by explosive welding were studied. It was found that, during explosive welding, an intermediate layer 20⋯40 μm thick with a finely dispersed heterophase structure, formed between the welded copper and tantalum plates. The structure of the layer was studied by scanning and transmission electron microscopy. Microvolumes with tantalum particles distributed in a copper matrix and microvolumes of copper particles in a tantalum matrix were detected. The tantal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In the present work the most regions inside the solidified melt zones near the Ta/Cu interface, were indexed as 'pure' Ta or Cu, with some quantity of not or mis-indexed pixels [11,30,31]. Figure 5a shows an SEM/EBSD image with a vortex region along the SS/Cu interface.…”
Section: Ta/cu Interfacementioning
confidence: 90%
See 3 more Smart Citations
“…In the present work the most regions inside the solidified melt zones near the Ta/Cu interface, were indexed as 'pure' Ta or Cu, with some quantity of not or mis-indexed pixels [11,30,31]. Figure 5a shows an SEM/EBSD image with a vortex region along the SS/Cu interface.…”
Section: Ta/cu Interfacementioning
confidence: 90%
“…The Cu-Ta system is characterized by nearly zero mutual solubility of the components in the solid-state [28,29] and high structural and mechanical stability at elevated temperatures. Greenberg et al [30], Maliutina et al [31] as well as Bataev et al [11] have shown that explosively welded Ta and Cu sheets exhibit a heterophase mixture in the reaction region with the size of the dispersed Ta and Cu particles similar to those of colloids. As also documented by Bataev et al [11] and Parchuri et al [32], the Ta x Cu 1-x based intermetallics or decagonal quasicrystals were found to coexist along with pure Ta and Cu particles in the solidified melt zones at the Ta/Cu interface.…”
Section: Macro-/meso-scale Interfaces Overviewmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the width of these layers is considerably smaller than after TIG welding [5,6]. The probability of unfavorable structure formation is reduced by the use of the explosion welding technique due to a high speed of the process, but, at the same time, the appearance of mixed zones of welded materials is not excluded [10][11][12][13][14]. Contact welding defects are an intensive mechanical mixing of materials due to the applied load, and diffusion processes [8,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%